Quality of experience assessment in virtual/augmented reality serious games for healthcare: A systematic literature review. - Laghari, Asif Ali; Estrela, Vania V.; Li, Hang; Shoulin, Yin; Khan, Abdullah Ayub; Anwar, Muhammad Shahid; Wahab, Abdul; Bouraqia, Khadija (Technology & Disability, 2024)
Virtual reality (VR) gaming (VRG) captures, examines, analysis, and renders the game data virtually instead of the users' devices over efficient networks. E.g., VR is crucial in visually guided surgery and manifold therapies. Video Quality Assessment (VQA) helps VRG software and devices execute high-quality inputs/outputs. This paper debates VRG processes, environments, VQA metrics, Quality of Experience (QoE), platforms, current methods, tools, use in medicine, existing operational gains/challenges, and highlights future directions.